Thermal tolerance in neotropical savanna tree species: exploring the temperature dependencies of photosynthesis in a diverse biome - Oliveira, Tony César de Sousa (2024)
Global climate changes have undeniably affected tropical vegetation. Evidence points out an increase in the aridity and temperature in the Brazilian Cerrado, the largest and most diverse savanna on the planet, which could push the species in this region toward their thermal limits. Therefore, understanding the thermal tolerance of plant species in this region is needed for a deeper comprehension of Cerrado\'s vulnerability to global warming. In this context, the goal of this thesis was to analyze the response of the photosynthetic apparatus and the mechanisms of acclimation and regulation of photosynthesis in Cerrado tree species. Firstly, to overcome methodological limitations, a rapid and effective approach was developed to estimate the temperature dependency on the maximum leaf carboxylation capacity (Vcmax) in situ. In the second chapter, a temperature-dependent scaling factor for the \"One-point method\" (OPM-ρ) was proposed and tested on 31 species from both Brazilian savannas and the Amazon forest. The approach resulted in a reduction of the overestimation of the apparent Vcmax rate (V\'cmax-ρ) at leaf temperatures above 35°C previously observed in the original OPM model. Additionally, in the third chapter, it was tested the use of V\'cmax-ρ as an alternative to Vcmax from traditional A-Ci curves (net photosynthesis, A, vs intercellular CO2 concentration, Ci). As a result, using V\'cmax-ρ at different temperatures (at least at 5 points) provided precise values for key temperature dependency parameters in photosynthesis: V\'cmax-ρ at 25°C (V\'cmaxρ_25), activation energy (Ea-ρ), entropy term (ΔS-ρ), deactivation energy (Hd-ρ), and optimal temperature for V\'cmax-ρ (ToptV-ρ). In the fourth chapter, the components of acclimation to the temperature dependency of photosynthesis in Cerrado species in two contrasting regions were evaluated. The analyses focused on species in two opposite regions of the Cerrado, specifically in the northeast and southeast supercenters, contrasting in their climatic conditions. The study considered widely distributed species (occurring in both regions) and those restricted to each region. The difference in ToptV-ρ values between regions and the geographic distribution range of species (wide and restricted) was analyzed. Additionally, the influence of leaf concentrations of nitrogen (N), phosphorus (P), potassium (K), and magnesium (Mg) on the regulation of ToptV-ρ was tested. In this chapter, it was observed that ToptV-ρ values did not differ between regions or geographic distribution of species. However, idiosyncratic relationships were identified between ToptV-ρ values and leaf P and K. Finally, in the fifth chapter, the role of thermal tolerance of photosystem II (PSII) in determining the upper limit of net photosynthetic (Asat) for the studied species was investigated. For the studied species, the temperature at which an initial decline (15%) and 50% of the maximum light-adapted efficiency of PSII (Fv\'/Fm\') occurred (Tcrit and T50, respectively), the optimal temperature for electron transport rate (ETR) and Asat (Topt_ETR and ToptA, respectively), and the thermal safety margin of PSII (SM) (the temperature range between Tcrit and Topt-ETR) were evaluated. Similar to ToptV-ρ values, a consistent PSII thermal tolerance was noted in all studied species, regardless of their geographical distributions. However, a positive relationship was identified between ToptA values with Tcrit, T50 and Topt_ETR. Additionally, it was found that Tcrit values consistently remained 2 to 5°C below Topt_ETR. These findings suggest that ecological strategies can multifacetedly influence the performance of Cerrado species, whose sensitivities vary across different biomes. It\'s further emphasized that OPM-ρ represents a significant advancement in the field, providing rapid photosynthesis measurements and valuable information on the deactivation energy of Rubisco. This information can potentially enhance the accuracy of ToptV-ρ estimates, which is crucial for global vegetation models.